Signaling pathway-focused gene expression profiling in pressure overloaded hearts - Marco Musumeci; Sonia Maccari; Elisa Corritore; Alessia Massimi; Tonino Stati; Giuseppe Marano; Liviana Catalano (Istituto Superiore di Sanità, 2011)
The β-blocker propranolol displays antihypertrophic and antifibrotic properties in the heart subjected to pressure overload. Yet the underlying mechanisms responsible for these important effects remain to be completely understood. The purpose of this study was to determine signaling pathway-focused gene expression profile associated with the antihypertrophic action of propranolol in pressure overloaded hearts. To address this question, a focused real-time PCR array was used to screen left ventricular RNA expression of 84 gene transcripts representative of 18 different signaling pathways in C57BL/6 mice subjected to transverse aortic constriction (TAC) or sham surgery. On the surgery day, mice received either propranolol (80 mg/kg/day) or vehicle for 14 days. TAC caused a 49% increase in the left ventricular weight-to-body weight (LVW/BW) ratio without changing gene expression. Propranolol blunted LVW/BW ratio increase by approximately 50% while causing about a 3-fold increase in the expression of two genes, namely Brca1 and Cdkn2a, belonging to the TGF-beta and estrogen pathways, respectively. In conclusion, after 2 weeks of pressure overload, TAC hearts show a gene expression profile superimposable to that of sham hearts. Conversely, propranolol treatment is associated with an increased expression of genes which negatively regulate cell cycle progression. It remains to be established whether a mechanistic link between gene expression changes and the antihypertrophic action of propranolol occurs.